2007
DOI: 10.1111/j.1939-1676.2007.tb03046.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biological Variance of Cystatin C in Comparison With Other Endogenous Markers of Glomerular Filtration Rate in Healthy Dogs

Abstract: Background: The aim of the study was to investigate and compare components of variance of endogenous markers of glomerular filtration rate (GFR) in healthy dogs and impact on the interpretation of results.Hypothesis: Cystatin C (cysC) in the dog is superior to creatinine (crea) and urea in detecting decreased renal function because of a high index of individuality (IoI).Animals and Method: Variance components of cysC, crea (2 methods: crea E , crea J ), urea, and inorganic phosphate (Pi) in plasma were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 21 publications
1
17
3
3
Order By: Relevance
“…In previous veterinary reports, a polyethylene PETIA was shown to reliably measure canine serum Cys-C [2,6,15,20,28]. Almy et al [2] showed that Western blot analysis demonstrated considerable cross-reactivity of the rabbit polyclonal anti-human Cys-C antibody with canine Cys-C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous veterinary reports, a polyethylene PETIA was shown to reliably measure canine serum Cys-C [2,6,15,20,28]. Almy et al [2] showed that Western blot analysis demonstrated considerable cross-reactivity of the rabbit polyclonal anti-human Cys-C antibody with canine Cys-C.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, the serum Cys-C concentration in dogs was measured by polystyrene PETIA [2,6,15,20,28]. However, it is difficult to use the polystyrene PETIA method for the measurement of canine serum Cys-C concentration in Japan, because this method is unavailable in Japanese commercial laboratories.…”
mentioning
confidence: 99%
“…A depuração de creatinina endógena é uma das mais utilizadas apesar de não ser um procedimento simples (TRALL et al 2015). Para a realização da depuração ou cleareance de creatinina, deve-se mensurar tanto a creatinina sérica quanto a urinária; pode ser usado o método colorimétrico, que é um teste cinético baseado na reação de creatinina com picrato alcalino (HALL et al 2014) ou o enzimático que mensura tanto a creatinina quanto a ureia no soro sanguíneo de humanos e animais (PAGITZ et al 2007). Com a finalidade de estimar a taxa de filtração glomerular (TFG), pode-se mensurar o clearance de creatinina (Ccr) em período de 24 horas.…”
Section: Depuração De Creatininaunclassified
“…De acordo com Pagitz et al (2007) a cistatina C pode ser mensurada tanto no soro quanto na urina de humanos e nos de cães, através do ensaio comercial de imunoturbidimetria de partículas; e atualmente o imunoensaio de nefelometria reforçada (PENIA) está sendo utilizado no soro e urina de humanos, porém devido ao seu alto custo esse método ainda não é utilizado na veterinária (GHYS et al 2014).…”
Section: Cistatina Cunclassified
“…In dogs, serum cystatin C may be an alternative to serum creatinine for screening dogs with decreased GFR due to chronic renal failure (Almy et al 2002). Nevertheless, Pagitz et al (2007) showed that the biological variance of cystatin C and creatinine in the serum of dogs is similar.…”
Section: Cystatin Cmentioning
confidence: 99%